RETROSPECTIVE ANALYSIS ON TYPES OF SUTURE MATERIALS USED IN NECK DISSECTION FOR PATIENTS UNDERGOING CANCER SURGERY IN PRIVATE DENTAL UNIVERSITY HOSPITAL - Pooja, J. Chandra; Jagadish, V.; Jeevanandan, Ganesh (International Journal of Psychosocial Rehabilitation, 2025)
Selection of appropriate suture material is of immense importance in the matter of wound healing. By the term suture,the material by which two surfaces are kept in position. The time of removal of sutures , size and types of suture used , also determine the quality of healing. Especially the healing of surgery wounds of neck dissection in cancer patients. The aim of the study is to evaluate the type of suture materials used in neck dissection for cancer patients undergoing neck dissection. A retrospective study was carried out by reviewing, analysing the data of 86000 patient between June 2019 to March 2020, among which 32 patients were selected who reported to the Department of Oral surgery and oral oncology for neck dissection.The various suture materials preferred for wound closure were collected from the patient records and tabulated on a spreadsheet. The collected data was analysed by computer software SPSS version 21 using Chi square test with the level of significance with age,gender and most preferred suture material.The highest number of cancer patients were found under the age group of 50 years (37.84%) and was most prevalent among male patients(81.08%) .The extra oral suture materials used were ethilon (56.76%) , silk(40.54%) and nylon(2.70%) with the most commonly used suture material being ethilon due to its superior qualities.The suture material used had no significant association with age(p value-0.32) and gender(p value-0.649). The most preferred suture material was ethilon due to its superior qualities